American presidents attend the theatre : the playgoing experiences of each chief executive - Bogar, Thomas A., 1948- (McFarland & Co., 2006)
"Not every presidential visit to the theatre is as famous as Lincoln's last night at Ford's, but American presidents attended the theatre long before and after that ill-fated night. This volume examines presidential theatre-going as it reflects shifting popular tastes in America. It provides a chronology of theatre attendance throughout the lives of all 43 American presidents"--Provided by publisher